Eksplorasi Pengalaman Guru Sekolah Dasar dalam Mengimplementasikan Pembelajaran Berdiferensiasi pada Kurikulum Merdeka - Gemala Widiyarti; Rini Aspita Br Bangun; S. Dameria Pandiangan; Novalia Paragaye; Della Agnesia Damanik (Civiliza Publishing, Indonesia., 2026)
The implementation of the Independent Curriculum (Kurikulum Merdeka) promotes differentiated learning as a key strategy for student-centered education. However, elementary school teachers still face challenges in addressing students’ diverse learning needs. This study aimed to explore elementary school teachers’ experiences in implementing differentiated learning in Deli Serdang Regency. A qualitative phenomenological approach was employed. Participants were selected using purposive sampling. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through triangulation and member checking. The findings revealed that teachers generally understood and implemented differentiated learning by adapting content, learning processes, and learning products to students’ needs. This approach increased students’ engagement, motivation, participation, and self-confidence during learning. Nevertheless, teachers encountered several challenges, including limited instructional time, large class sizes, difficulties in conducting diagnostic assessments, developing differentiated teaching materials, and limited learning facilities. To address these challenges, teachers collaborated through Teacher Working Groups (KKG), participated in professional development programs, and utilized the Merdeka Mengajar Platform. The study concludes that differentiated learning has been implemented reasonably well in elementary schools in Deli Serdang Regency. However, strengthening teacher competency, school leadership support, and adequate educational resources remains essential to optimize the implementation of the Independent Curriculum and student-centered learning.